Determining the phytoremediation potential of naturally growing tropical plant species at a sanitary landfill - Rajoo, S. Keeren; Ismail, Ahmad; Karam, S. Daljit.; Abdu, Arifin; Norul Izani; Gerusu, Geoffery James; Ibrahim, Zahari; Abdullah, Muhammad Amin; Ibrahim, Mohd Hakeem (Malaysian Society of Soil Science, 2023)
Heavy metal contamination poses severe threats to ecosystems and human health, necessitating effective remediation strategies. Phytoremediation, which leverages plants to remove heavy metals, offers a promising solution. However, this approach remains underexplored, particularly in tropical ecosystems like Malaysia. Thus, this study examines the potential of native plant species in addressing heavy metal pollution, at Air Hitam Sanitary Landfill (AHSL). This location was selected due to it being an urban ecosystem that is susceptible to soil heavy metal contamination from municipal waste disposal and atmospheric deposition. Native plant species, namely Pueraria phaseoloides, Dicranopteris linearis, Cyperus rotundus, Acacia spp., and Melastoma malabathricum were found to grow well at AHSL, thus were selected for this study. The phytoremediation potential of these plant species were determined by calculating their translocation (TF) and bioaccumulation factors (BCF). Based on the TF and BCF values of all the plants studied, none of the plant species were potential phytoremediators. However, four plant species were identified as potential bioindicators of Cd. These species were Pueraria phaseoloides, Cyperus rotundus, Acacia spp. and Melastoma malabathricum. In conclusion, this study underscores the importance of understanding phytoremediation potential within challenging environments and its contribution to heavy metal mitigation. By investigating native plant species in AHSL, the research aids in expanding the application of phytoremediation strategies, ultimately fostering ecological restoration, and safeguarding human health.